2018
DOI: 10.1038/s41419-018-0867-4
|View full text |Cite
|
Sign up to set email alerts
|

XAF1 forms a positive feedback loop with IRF-1 to drive apoptotic stress response and suppress tumorigenesis

Abstract: X-linked inhibitor of apoptosis (XIAP)-associated factor 1 (XAF1) is a proapoptotic tumor suppressor that is frequently inactivated in multiple human cancers. However, the molecular basis for the XAF1-mediated growth inhibition remains largely undefined. Here, we report that XAF1 forms a positive feedback loop with interferon regulatory factor-1 (IRF-1) and functions as a transcriptional coactivator of IRF-1 to suppress tumorigenesis. Under various stressful conditions, XAF1 transcription is activated by IRF-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 42 publications
(71 reference statements)
3
48
1
Order By: Relevance
“…The alternative splice site in exon 5 results in a large deletion of exon 5 (Fig 7E), but in-frame translation of exon 6. Importantly, the C-terminal domain is thought to be essential for binding to XIAP (31), and short isoforms are thought to function as dominant negative (22, 23), suggesting that these strain differences may lead to functional changes in XAF1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative splice site in exon 5 results in a large deletion of exon 5 (Fig 7E), but in-frame translation of exon 6. Importantly, the C-terminal domain is thought to be essential for binding to XIAP (31), and short isoforms are thought to function as dominant negative (22, 23), suggesting that these strain differences may lead to functional changes in XAF1.…”
Section: Resultsmentioning
confidence: 99%
“…Full-length isoforms are frequently downregulated in human tumors, while truncated isoforms are upregulated. Importantly, short forms have been reported to have dominant negative effects (22, 23).…”
Section: Introductionmentioning
confidence: 99%
“…X-linked inhibitor of apoptosis protein (XIAP)-associated factor 1 (XAF1) is identified as a pro-apoptotic protein and an antagonist of XIAP, counteracting anti-caspase activity of XIAP (43). It was demonstrated that XAF1 may promote cell apoptosis through in a multi-mechanism environment (44)(45)(46)(47). Down-regulated or deleted of XAF1 was observed in many malignancies, which suggesting that low expression of XAF1 may promote malignant tumor progression by relieving tumor cell apoptosis inhibition (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that, XAF1 as a proapoptotic tumor suppressor is always inactivated in multiple human cancers. XAF1 was identi ed ubiquitously in all normal adult and fetal tissues but was present in very low levels in a variety of cancer cell lines [41][42][43][44][45]. Both IFN-α2 and IFN-β were found to induce XAF1 transcription.…”
Section: Discussionmentioning
confidence: 99%